KARAKTERISTIK MARSHALL CAMPURAN ASPAL BUTON TIPE CPHMA DENGAN PENAMBAHAN ABU BATU - Tipawael, Stevany Brenda; Siahaya, Vera Th. C.; Huwae, David Daniel Marthin (Jurusan Teknik Sipil, 2024)
Roads are transportation infrsstructure that connects one area with other areas, especially in the transportation sector for the smooth flow of goods and services. Roads experience damage due to the incereasing volume and load of vehicles, especially if they are always passed by heavy vehicles that are overloaded. The Namlea - Marloso road section has a length of 19,026 km with a road width of 4.0 m. This road section has road damage to the road surface layer in the form of cracks, holes, and surface defects. Previously damaged road conditions have been repaired by patching using CPHMA. However, the planned life of the road is in fact not in accordance with what is happening in the field. The road has been damaged ± 4 months after being repaired. The aim of the research was to determine the marshall characteristics of CPHMA-type Buton asphalt mixture using rock ash as filler and to analyze the percentage of rock ash content that met the requirements for Buton CPHMA-type asphalt mixture. This study used rock ash with the addition of 4%, 8% and 12%. This test was carried out using a Marshall test kit with reference to the 2020 Bina Marga Specifications and the Indonesian National Standard (SNI). The research results show that the average values obtained are density value =2.21 gr/cc, marshall stability value =1416 kg, flow velue =3.02 mm,, VMA value =18.24%, VIM value =7.72%, VFB value =63.18%, MQ value =483.02 kg/mm. marshall CPHMA characteristics with the addition of rock ash resulted in increased stability, flow, VMA and VIM values. While the values of VFB and MQ decreased. Presentation of optimum rock ash addition content =6% and meets the 2018 Bina Marga specification revision 2.